Digital Marketing Content Involving Consumers At PT. Bela Berlian Mandiri - Berlian Erlangga; Hanifa Nur Fadhilla (Cita konsultindo, 2024)
This research aims to analyze the effectiveness of digital marketing strategies implemented by PT Bela Berlian Mandiri, focusing on the use of Instagram as a marketing platform. Considering the advancement of technology and the increase in social media usage, the company needs to adapt to innovative marketing methods to remain competitive. This study explores various types and strategies of digital marketing, including paid promotions on Instagram, and evaluates the benefits and challenges faced by the company. Data were collected through interviews with employees and consumers of PT Bela Berlian Mandiri as well as sales data analysis. The research results show that the use of digital marketing strategies through Instagram has a positive impact on increasing the company's brand awareness and sales. However, several obstacles need to be addressed for further optimization. Recommendations are made for the development of more effective digital marketing strategies in the future.